A Micro-Level View of CSR: A Hospitality Management Systematic Literature Review. (August 2020) - Guzzo, Renata F.; Abbott, JéAnna; Madera, Juan M.
This study provides a systematic review of corporate social responsibility (CSR) in the hospitality management literature over the last decade. In contrast to prior reviews, this article starts from a broader analysis, followed by a narrower, micro-level examination of the hospitality management literature that links CSR to customers' and employees' attitudes and behaviors. The findings of this review show that researchers study CSR primarily from a meso-level perspective of how CSR is developed and implemented by organizations, and how it influences financial performance. This study found that although employees have long been crucial stakeholders in service environments, hospitality researchers have only recently begun to focus on understanding the relationships between CSR and employee behaviors and attitudes. This study provides directions for future research by identifying research gaps and comparing the results of this review with those of organizational psychology and management reviews.